Evaluasi Pelatihan Bidang Kesehatan Menggunakan Model Evaluasi Kirkpatrick: Systematic Review - Tinurbaya, Afriani; Bachtiar, Adang; Oktamianti, Puput (GEMA EKONOMI, 2023)
In relation to the importance of health for every human being, the Ministry of Health provides a large enough budget for improving the quality of health workers through training. However, the evaluations commonly used to measure training effectiveness are generally limited to pre-test and post-test to assess participants' knowledge before and after training (Kirkpatrick level 2 evaluation model). The Kirkpatrick evaluation model is a training evaluation model that is often used to measure the effectiveness of training, namely by measuring the achievement of results based on four levels (level 1 – level 4). Therefore, the authors intend to investigate various literature related to the evaluation model from various levels, which can be developed to evaluate the training of health workers by the Ministry of Health. This literature review follows PRISMA guidelines. Database searches were carried out through PubMed, Scopus and ProQuest search channels in the last 5 years (2017-2022). The results show that level 2 evaluation is most often used to assess the effectiveness of health training outcomes, namely by assessing the improvement of participants' knowledge and skills after training. Fewer level 3 and level 4 evaluations are conducted due to limited time, funds, experience, and tools. However, since each level in Kirkpatrick's evaluation model is interrelated, it is important to be able to evaluate each level sequentially so that information related to training effectiveness can be clearly depicted. Therefore, the Ministry of Health needs to prepare all the necessary resources to be able to assess the effectiveness of training at each level.